Factors affecting facial nerve outcome in vestibular Schwannoma surgery - Jha, Rajiv; Shrestha, Rajendra; Rajbhandari, Binod; Bhattarai, Sushil Mohan; Aryal, Sameer; Gautam, Sindhu; Jha, Binit; Karki, Anuj Jung (Nepal Journal of Neuroscience, 2024)
Background: Preservation of facial nerve injury is a key important factor in vestibular schwannoma surgery as facial paralysis has devastating functional and psychological consequences for patients. Objective: To correlate different factors resulting in facial nerve preservation in vestibular schwannoma surgery by retro mastoid retro sigmoid approach. Method: This is a retrospective analysis of facial nerve status of 212 cases of vestibular schwannoma microsurgery through Retrosigmoid Retromastoid (RSRM) approach. This study was carried out in National Neurosurgical Referral Center(NNRC), National Academy Of Medical Sciences (NAMS), Bir hospital between January 2016 to December 2022.Preoperative and post operative details of facial nerve function status compared according to House and Brackmann (H and B) grading system, and factors influencing outcome in facial nerve preservation were analyzed. Recurrent and residual tumors were excluded. Results: A total of 212 cases of vestibular schwannoma were operated during the study period. The average age of presentation was 47 years. Most common affected age group was 51-60 years. Female to male ratio was 3:2.5. The most common clinical symptoms for vestibular schwannoma were sensorineural hearing loss followed by headache and difficulty in limb coordination. Tumor size and consistency was most important indicator of facial nerve function outcome. Conclusion: The incidence of post operative facial palsy is found to be correlated to tumor size and consistency. Improvement of the facial nerve outcome is detected in patients undergone simultaneous intraoperative monitoring (IONM).